2019
DOI: 10.4038/jnsfsr.v47i1.8929
|View full text |Cite
|
Sign up to set email alerts
|

Durability properties of alkali pozzolan cement (APC)

Abstract: This paper compares the durability properties (HVFA) cement and ordinary Portland cement (OPC). The susceptibility to durability issues was investigated through the water absorption test using 28-day-old samples. Durability against chemical attacks was investigated through sulphuric 1-year-old samples. The results indicated that APC occupies a and greater resistance than OPC for sulphuric acid attack and chloride ion penetration. Chemical and microstructural reasons for the above behaviours are presented. A ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…When NS reacts with Ca(OH) 2 , it creates an alkaline environment that accelerates the dissolution of active alumina and silica in the cement–pozzolan–water system. Studies have revealed that cementitious materials with fly ash and slag can benefit from sulphate-forming ettringite, which enhances their mechanical properties [ 30 , 31 ]. NS-activated mortars exhibit less shrinkage than silicate-activated mortars because of the creation of more ettringite crystals [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…When NS reacts with Ca(OH) 2 , it creates an alkaline environment that accelerates the dissolution of active alumina and silica in the cement–pozzolan–water system. Studies have revealed that cementitious materials with fly ash and slag can benefit from sulphate-forming ettringite, which enhances their mechanical properties [ 30 , 31 ]. NS-activated mortars exhibit less shrinkage than silicate-activated mortars because of the creation of more ettringite crystals [ 32 ].…”
Section: Introductionmentioning
confidence: 99%